Análisis de los sistemas de recaudaciones de los impuestos municipales del GAD municipal de Quevedo en los años 2013 – 2014 - Macías García, Amparo del Rocío (2016)
This research was performed as a field design evaluative and aimed to determine the collection of municipal taxes in the canton GAD Quevedo For the execution of the research was done using a range of techniques such as observation, documentation and survey. This was applied to a selected sample of 400 people, which constitute the universe under study, and therefore it was a census sample. For it was designed a data collection instrument in the form of a questionnaire.Once the required information, we proceeded to process the results, analyzing them, using a quantitative and qualitative approach, so that the results of the observation were analyzed qualitatively, in the presence of certain traits that allowed assessment tax collection process in the municipality. For quantitative analysis, techniques of descriptive statistics were used in the question of alternatives, through frequencies and percentages that show the results of the questionnaire application and so were finally obtained the findings, among which stand out the existence of a set of difficulties in the process of tax collection, recommending its prompt solution.